Shadows of Self [compact disc, unabridged] - Sanderson, Brandon (Sanderson, Brandon. Mistborn., 2015)
Mistborn's society is evolving as technology and magic mix, the economy grows, democracy contends with corruption, and religion becomes a growing cultural force, with four faiths competing for converts.